Pencapaian Generativitas Mantan Narapidana Tindak Pidana Korupsi Dewasa Tengah - Melynda Narawika Rengganis (Jurnal Penelitian Kualitatif Ilmu Perilaku, 2020)
The purpose of this study in detail is to know how the Attainment of Generativity to former Corruption Prisoners. This research was conducted by using qualitative method with phenomenology technique using three subjects 2 men, and 1 woman who had been in the prison because of corruption case. The results show that Former Prisoners can reach Generativity they interpret generativity as an attempt to actualize in order to transmit subject experiences to others and they need for their self-acceptance, the three of subjects are actually just victims of a policy or system that eventually makes them change the status of being suspect. Generativity can be achieved by them because of support for their family, friends, and people around the subject. And for further research is expected to conduct more extensive research because in the context of this study only untouchable excorruption inmates especially middle aged.